Engineering optoelectronics and smart sensors leveraging metal-organic framework materials - Möslein, AF (2022)
Metal-organic frameworks (MOFs) have emerged as promising nanomaterials for the development of advanced sensing technologies. Indeed, their unparalleled features comprising structural diversity, tailorability, high porosity, large surface area, and adsorption affinities can offer superior sensing performance unattainable by the array of conventional materials for selective, fast, and sensitive detection of gases. However, for the integration of MOFs into sensor devices, a thorough understanding of the material’s underpinning properties and mechanisms is vital. In this integrated thesis, the key principles, which are used for functionalising MOFs with desired properties, are studied from the single-crystal level (Chapter 1). Herein, Chapter 2 introduces near-field infrared spectroscopy techniques for the chemical characterisation of individual MOF-type crystals at the nanoscale.